2014
DOI: 10.7314/apjcp.2014.15.5.2257
|View full text |Cite
|
Sign up to set email alerts
|

C1420T Polymorphism of Cytosolic Serine Hydroxymethyltransferase and Risk of Cancer: a Meta-analysis

Abstract: A series of studies have explored the role of cytosolic serine hydroxymethyltransferase (SHMT1) C1420T polymorphism in cancer risk, but their results were conflicting rather than conclusive. To derive a more precise estimation of the association between C1420T and cancer risk, the present meta-analysis of 28 available studies with 15,121 cases and 18,023 controls was conducted. The results revealed that there was no significant association between the polymorphism and cancer risk overall. In stratified analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Previously, Vijayakrishnan and Houlston25 conducted a systematic review and meta-analysis of 2 published studies,16,19 which included 697 cases and 1038 controls, the results shown that SHMT1 rs1979277 heterozygotes may reduce the risk of ALL 25. Zhong et al26 also conducted a meta-analysis including 4 published studies15,17–19 consisted of 1494 cases and 1721 controls, the results also showed that 1420T allele was a protective factor for leukemia. The difference between results of the fore-mentioned 2 meta-analyses and this study may because of the small sample size and the populations they have included.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, Vijayakrishnan and Houlston25 conducted a systematic review and meta-analysis of 2 published studies,16,19 which included 697 cases and 1038 controls, the results shown that SHMT1 rs1979277 heterozygotes may reduce the risk of ALL 25. Zhong et al26 also conducted a meta-analysis including 4 published studies15,17–19 consisted of 1494 cases and 1721 controls, the results also showed that 1420T allele was a protective factor for leukemia. The difference between results of the fore-mentioned 2 meta-analyses and this study may because of the small sample size and the populations they have included.…”
Section: Discussionmentioning
confidence: 98%